Deformation pattern of the Lower Triassic sedimentary formations of the Silica Nappe: Evidence for dynamics of the Western Carpathian orogen - Vojtko,R.; Lacny,A.; Jerabek,P.; Potocny,T.; Geratova,S.; Kilik,J.; Plasienka,D.; Lexa,O. (Journal of Geosciences, 2023)
The Lower Triassic formations of the Silicic Unit were studied by structural geology methods to unravel its deformation history and chronology of nappe transport. The nappe sheet of this unit is the highest representative thin-skinned thrust in the Western Carpathians. The Silicic Unit spreads in the broader area of the Variscan consolidated Gemeric and the Veporic crystalline basements. Geological and palaeotectonic evidence indicate that the Silicic nappe pile is more than one km and at some places up to 3 km thick. The nappe is abundant in the inner zones of the Western Carpathians and overlaps all other structural units in the area, in particular it covers the margin of the Gemeric Unit. Based on the structural analysis, geometry and overprinting criteria of secondary planar structures (cleavages or fold axial surfaces) and fold axes indicate the presence of three main deformation events. Generally, the first group of structures is related to ≈ W-E shortening (AD1), which is interpreted in association with closure of the Meliata Ocean. The younger direction of the Silicic nappe system shortening (AD2) shows top-to-the-NNW thrusting and is related to the Early to Late Cretaceous Eoalpine convergence. This stage also comprises folds with steep north dipping axial surfaces and occasionally also flat-lying axial surfaces forming fan-like structure of fold axial planes. The last observed structures refer to the W-E shortening (AD3) characterised by the symmetric gentle to open folds with subvertical axial surfaces locally with few pronounced top-to-the-east asymmetries.
Keywords: Western Carpathians; Silicic nappe; thrusting; folding; tectonic transport